2020
DOI: 10.3390/vaccines8020201
|View full text |Cite
|
Sign up to set email alerts
|

A Durable Relationship: Respiratory Syncytial Virus Bronchiolitis and Asthma past Their Golden Anniversary

Abstract: Numerous preventive strategies against respiratory syncytial virus (RSV) are undergoing late stage evaluation in humans and, in addition to their intended benefit for acute illness, may impact long term consequences of infection in infants. Severe RSV infection has been repeatedly associated in the literature with long term complications, including impaired lung function, recurrent wheezing, and asthma. However, whether RSV lower respiratory tract infection (LRTI) causally affects the odds for developing wheez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 84 publications
2
24
0
1
Order By: Relevance
“…Consistent with prior study results, we found that patients with RSV and hMPV infections were more likely to be older and to suffer from underlying systemic diseases such as cancer [30,31]. The presence of myalgia was more often associated with influenza [32,33], whereas nasal congestion and dyspnea were more closely linked to RSV infection [34,35]. Indeed, wheezing and dyspnea are more characteristic of RSV infections in both infants and adults [34,36,37], likely owing to the fact that RSV exhibits a specific tropism for small airway epithelial cells, thus resulting in lower respiratory tract involvement.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with prior study results, we found that patients with RSV and hMPV infections were more likely to be older and to suffer from underlying systemic diseases such as cancer [30,31]. The presence of myalgia was more often associated with influenza [32,33], whereas nasal congestion and dyspnea were more closely linked to RSV infection [34,35]. Indeed, wheezing and dyspnea are more characteristic of RSV infections in both infants and adults [34,36,37], likely owing to the fact that RSV exhibits a specific tropism for small airway epithelial cells, thus resulting in lower respiratory tract involvement.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with prior study results, we found that patients with RSV and hMPV infections were more likely to be older and to suffer from underlying systemic diseases such as cancer [30][31]. The presence of myalgia was more often associated with in uenza [32][33], whereas nasal congestion and dyspnea were more closely linked to RSV infection [34][35]. Indeed, wheezing and dyspnea are more characteristic of RSV infections in both infants and adults [34,[36][37], likely owing to the fact that RSV exhibits a speci c tropism for small airway epithelial cells, thus resulting in lower respiratory tract involvement.…”
Section: Discussionsupporting
confidence: 88%
“…In children, RSV can lead to severe respiratory disease requiring hospitalization, and causes death in some rare cases. Other RSV symptoms common among infants include listlessness, poor or diminished appetite, and fever [16][17][18]. RSV and COVID-19 coinfection may increase the severity of disease in children.…”
Section: Symptoms Of Covid-19 and Rsv In Childrenmentioning
confidence: 99%